Efeitos das invasões massivas na diversidade funcional, abundância e distribuição dos peixes na planície de inundação do alto rio Paraná. - Angulo Valencia, Mirtha Amanda (2020)
The introduction of species is considered a problem for aquatic ecosystems on a global scale. Once established, non-native species can affect resident species through numerous interactions and modify the community structure of the local community. Traditionally, taxonomic diversity is used to understand the interactions between native and non-native species, but functional diversity provides more adequate tools to detect changes in communities. The objective of this study was to identify the impacts resulting from the coexistence of native and non-native fish species from the upper Paraná River floodplain, after more than thirty years of invasion (in a discontinuous time series from 1986 to 2018). The first approach dealt with the assessment of the functional diversity patterns of native and non-native species over time and in environments with varying degrees of regulation by dams, as well as the identification of the functional characteristics that most favor these groups of species. The second approach, assessed the variations imposed by non-native fish species on their native congenerics through abundance, distribution and nutritional condition, over time. The evaluation of the functional diversity of native and non-native fish species over time and in habitats with different degrees of environmental change has allowed us to infer potential impacts of non-native species on native species through changes in functional diversity patterns, such as such as richness, divergence and functional redundancy. Furthermore, it was observed that the distribution of the functional characteristics of native and non-native fish species in the lowlands has changed over time. The analysis of the coexistence of native and non-native phylogenetically related species allowed to identify that some species such as Ageneiosus militaris, Serrasalmus maculatus, Schizodon altoparanae and Schizodon nasutus, are gradually being replaced by congeneric non-native species. Given that all species play determined roles in their habitats, the exclusion of any of the native species can have negative consequences on ecosystem goods and services.